Spectrophotometric Estimation of Venlafaxine Hydrochloride and Ritodrine Hydrochloride - Sankar, D.G.; Vijayasri, K.; Snehalatha, B.; Murthy, T.K.; Kumar, J.M.R.; Reddy, M.V.V.N. (Asian Journal of Chemistry, 2010)
Simple and sensitive UV spectrophotometric methods for the determination of venlafaxine hydrochloride and ritodrine hydrochloride are developed and having maximum absorbance at 225 and 226 nm respectively and obey Beer's law in the concentration ranges of 5–25 μg/mL and 4–20 μg/mL respectively. These methods are extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives and diluents.